ANALISIS MAQASHID SYARI’AH PADA KEBIJAKAN RESTRUKTURISASI DALAM MENGATASI PEMBIAYAAN BERMASALAH AKIBAT PANDEMI COVID 19 (STUDI KASUS BANK BTN SYARIAH MEDAN) - Muallif Masyhuri; Azhari Akmal Tarigan; Fauzi Arif Lubis (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
Abstract The provision of financing in Islamic banks always carries the risk of payment difficulties that occur in Islamic banks the same as conventional banks, causing financing problems. To overcome this problem, Islamic banking applies the same thing as conventional banks, namely financing restructuring in overcoming problem financing. In this study, the problem that occurred was the COVID-19 pandemic which caused the business and business sectors to experience market problems due to government regulations to keep themselves at home. So the bank, in this case Islamic banking, took action to answer the problem of non-performing financing by restructuring to save banking liquidity and also the finances of customers who had difficulty paying due to the covid 19 pandemic. This study used a qualitative approach using the Publish and Perish software tool to collect journal articles relevant to the purpose of this study. The collected articles were analyzed for content (content analysis) and analyzed with the maqashid shari'ah theory to see the suitability of saving problematic financing for customers and banks during the covid 19 period to achieve benefit for both. The findings in this study are that in improving the performance of banks in carrying out non-performing financing, banks must analyze social problems that occur to find solutions due to the Covid 19 Pandemic which causes economic problems that result in problematic financing. Keyword : maqashid shari'ah, restructuring, non-performing financing